Oral health status of the tribal population of Chamarajanagar district, Karnataka - Ray, Shibani Sushmitha; Doddaiah, Sunil Kumar; N., Chandan; Gopi, Arun; M. R., Narayan Murthy; Bilimale, Anil S. (International Journal Of Community Medicine And Public Health, 2021)
Background: Regardless of the improvements in the field of healthcare, there is a section of people who live away from civilization known as indigenous people or tribals. Information regarding oral health status is instrumental in the planning and implementation of oral health policies and programmes related to promotion of oral health. The present study aimed to assess the oral health status of the tribal population of Chamarajanagar district. Methods: A cross‑sectional survey of 256 tribals of Chamarajanagar district was conducted. A modified WHO oral health assessment form 2013 was utilized and examined according to the WHO methodology 2013. The recorded data was statistically analysed using the statistical package for the social sciences version 24. Results: Based on the age-category, majority of them belonged to the age group of 35-44 years. All the participants belonged to the sub-caste of Soligas. The total decayed missing filled teeth (DMFT) among the subjects was 5.5±4.14, 114 (44.5%) of them had gingival bleeding, 76 (29.7%) of them had pockets of 4-5 mm depth, 14 (5.5%) of them had pockets of >6 mm depth, 74 (28.9%) had loss of attachment of 4-5 mm, 16 (6.3%) of them had loss of attachment of 6-8 mm, 3 (1.2%) had leukoplakia, 1 (0.4%) had lichen planus, 12 (4.7%) had ulceration and 12 (4.7%) had abscess. Conclusions: This study showed that a majority of tribes used toothbrush and toothpaste to routinely clean their teeth. High prevalence of dental caries and periodontal diseases was observed among the participants.